ANALISIS TITIK PULANG POKOK USAHA ABON AYAM PADA INDUSTRI RAJA BAWANG DI KOTA PALU - Saleha, Aprilia Dena; Antara, Made (AGROTEKBIS, 2018)
This research is a aimed to know the quantity of product, income and revenue shredded chicken industry at Raja Bawang in Palu when  it reaches the Break Even Point. The respondent on this research was chosen purposively, suc as the chaiman and labor to get accurate of the project aim. Breack Even Point Analysis was used as the analyzing tool. Results of research on the product packaging 100 g shredded chicken the revenue amounted Rp 18,750,000/month with a production cost is Rp 13,470,108/month so obtaining an income of Rp 5,279,892/month, whereas for product packaging shredded chicken 200 g revenues counted  Rp18,750,000/month with a production cost is Rp 11,000,274/ month so  obtaining an income of  Rp7,749,726. Break Event Point for shredded chicken packaging 100 g achieved on production of 325 packs at a price of 25,000 packaging then the sales value received is Rp 8,125,000/month, while the break even point for shredded chicken packaging 200 g achieved on the production of 78 packs with price 50,000/packaging then the sales value received is Rp 3,900,000/month.